Literature Review: Korelasi HBA1C dan Mean Platelet Volume (MPV) terhadap Kaki Diabetes - Mahdalena Mahdalena; Fauzia Noor Liani; Dewi Indah Noviana Pratiwi; Nanang Miftah Fajari; Azma Rosida (Homeostasis, 2021)
Abstract: Diabetic foot ulcers are a major complication of diabetes mellitus. The mortality rate for diabetic foot ulcers ranges from 17- 32% and the amputation rate ranges from 15-30%. Diabetic foot ulcers associated with HbA1c levels> 6.5 patients are considered to have poor glucose control which can lead to various complications. Hyperglycemia in diabetes can increase platelet reactivity so it is necessary to check the Mean Platelet Volume (MPV) which is a biomarker of platelet reactivity. This literature review aims to collect data and analyze the correlation of HbA1c and Mean Platelet Volume (MPV) on the incidence of diabetic foot and to understand the mechanisms underlying changes in HbA1c levels and Mean Platelet Volume (MPV) that cause complications of diabetic foot. Literature sources are 15 journals obtained through medical journal databases, namely Pubmed, Science Direct and Google Scholar with the criteria of using English and Indonesian in the period 2009-2020. The results obtained in this study were the mean level of mean platelet volume (MPV) based on 10 literatures was 13.089 fl. Mean HbA1c levels from 15 literature HbA1c> 8%. Keywords: correlation, kaki diabetes, diabetic foot ulcer, HbA1c, mean platelet volume. Abstrak: Ulkus kaki diabetes merupakan komplikasi utama diabetes melitus. Angka kematian ulkus kaki diabetes berkisar antara 17- 32% dan laju amputasi berkisar 15- 30%. Ulkus kaki diabetes dikaitkan dengan kadar HbA1c >6,5 pasien dianggap memiliki kontrol glukosa yang buruk yang dapat menyebabkan berbagai komplikasi. Hiperglikemia pada diabetes dapat meningkatkan reaktivitas trombosit sehingga perlu pemeriksaan Mean platelet Volume (MPV) yang merupakan biomarker reaktivitas trombosit. Literature review ini bertujuan untuk mengumpulkan data dan menganalisis korelasi HbA1c dan Mean Platelet Volume (MPV) terhadap kejadian kaki diabetes dan memahami mekanisme yang mendasari perubahan kadar HbA1c dan Mean Platelet Volume (MPV) yang menyebabkan terjadinya komplikasi kaki diabetes. Sumber literatur berupa 15 jurnal yang diperoleh melalui database jurnal kedokteran, yaitu Pubmed, Science Direct dan Google Scholar dengan kriteria menggunakan Bahasa inggris dan Bahasa Indonesia dalam kurun waktu 2009-2020. Hasil yang didapatkan dalam studi ini adalah Rerata kadar Mean Platelet Volume (MPV) berdasarkan 10 literatur adalah sebesar 13,089 fl. Rerata kadar HbA1c dari 15 literatur HbA1c>8%. Kata-kata kunci: hubungan, kaki diabetes, diabetic foot ulcer, HbA1c, mean platelet volume.